2010
DOI: 10.1080/10810730903528017
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Effects of Narrative as Culture-Centric Health Promotion

Abstract: Health promotion interventions designed for specific cultural groups often are designed to address cultural values through culturally adapted messages. Recent trends in health promotion incorporate narrative theory, locating culture within the narratives of cultural members, and suggesting that narrative may provide a central, grounded medium for expressing and shaping health behavior. We suggest that culturally grounded narratives are a natural choice for identifying and shaping health messages for specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(184 citation statements)
references
References 70 publications
2
179
0
3
Order By: Relevance
“…In contrast to the assumption that in order to be effective, health promotion messages should always be tailored to the culture of the target group (Kreuter et al, 2005;Larkey & Hecht, 2010) and this study found that a fotonovela developed for a Latin-American audience with low literacy also had positive effects on health knowledge of Dutch adults with varying levels of literacy. An explanation may be that readers readily get captivated by a well-told story, even if it plays in a cultural context that greatly differs from the reader's own reality.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In contrast to the assumption that in order to be effective, health promotion messages should always be tailored to the culture of the target group (Kreuter et al, 2005;Larkey & Hecht, 2010) and this study found that a fotonovela developed for a Latin-American audience with low literacy also had positive effects on health knowledge of Dutch adults with varying levels of literacy. An explanation may be that readers readily get captivated by a well-told story, even if it plays in a cultural context that greatly differs from the reader's own reality.…”
Section: Discussionmentioning
confidence: 55%
“…However, the authors remark that "evidence to support this notion is surprisingly limited" (p. 53). Larkey and Hecht (2010) also regard culturally grounded narratives as a natural choice for creating health messages for specific audiences, pointing out that many health promotion campaigns include interventions based on the assumption that in order to be effective, the messages should incorporate culturally relevant content. Just as Kreuter et al (2005), however, Larkey and Hecht remark that hardly any studies have tested whether such approaches are indeed more effective than programs that ignore culture (pp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, communication in local dialect is important for reaching out to the population of concern [1]. Interventions which target behavior change amongst the population of concern should be based on thorough understanding of the target population culture as well as ethnicity [2]. The health message hence can be tailored in a way which makes it culturally relevant and can help us achieve expected outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it becomes essential not only to measure media-relevant outcomes (e.g., knowledge and realism) and behavior-relevant outcomes (e.g., attitudes and behaviors) of a media literacy intervention, but also to include measures of interpersonal communication about the intervention in evaluations to assess social proliferation [54,55]. This article presents interpersonal communication as a moderator of a media literacy curriculum [Youth Message Development (YMD)] targeted at preventing high school student alcohol use.…”
Section: Interpersonal Communication Outcomesmentioning
confidence: 99%